ANÁLISIS DE LA SEGURIDAD INFORMÁTICA DE LA RED DE LA GOBERNACIÓN DE LA PROVINCIA DE LOS RÍOS. - ASITUMBAY ALUCHO, FRANKLIN ARMANDO (2018)
The ability to prevent, respond and recover from any type of incident caused by any factor that is natural or caused by the human being as well as the various natural disasters depending on the impact caused in society in relation to local security and provincial; The Government of the Province of Los Ríos being a governmental institution in charge of promoting citizen security where technology more than fulfilling an important role becomes a strategic ally to face adverse problems; Also, maintain the ability to coordinate a correct communication with the other entities and estates of the Ecuadorian state in order to provide immediate solutions to the vicissitudes of the moment. For this reason, an analysis of the computer security of the network of the Government of the Province of Los Ríos is carried out with the objective of identifying the critical points as well as the critical areas and vulnerable sectors of the data network of the entity that It is the object of study. Additionally, it is intended to provide a case study in which the importance of maintaining a controlled environment with communication systems and channels for a perfect coordination with elements and external help whether local, state, non-governmental and voluntary; with which greater exploitation and exploitation of the available resources and capacities of the institution's infrastructure is obtained.